Educational potential of Facebook use in higher education - DÜVENCİ, ABDULLAH (My University, 2021)
In the last decade, social media gradually increased their popularity on daily routines since people have accustomed to the new information and communication technologies. In terms of university students, the popularity of the internet is obvious, with the fact that their intense mood for searching adventures usually end up in social media. This study examined social media, particularly Facebook’s use in higher education as a Learning Management System (LMS). The method employed in this research is meta-synthesis pattern in which 205 articles from SCI-Expanded and SSCI indexes were reviewed. According to the inclusion-exclusion criteria, 175 articles were eliminated and only 30 articles were deeply reviewed under three main themes, which are “learning, interaction, transition and adaptation.” Descriptive results did not reveal that any research study before the year of 2009 dealing with these three main themes. In addition to this, the remarkable number of studies (n=6) were conducted in 2015 and 2016. All the examined studies were conducted in 16 different countries and quantitative methods and small sample sizes were generally preferred in those research studies. Considering the findings of those examined studies, Facebook as social media tool can be one of the best LMS option for higher education.
Keywords: higher education; educational use; Facebook; social media; research trends; lms